Metode Couple Linear Congruential Generator (CLCG) untuk Ujian Sekolah Berbasis Web - Cendra Wadisman; Irohito Nozomi (INTECOMS: Journal of Information Technology and Computer Science, 2019)
IN SMA N 2 Kota Pariaman school exams still use the answer sheet media at the time of publication. After the exam is complete the answer sheet of the exam will also be corrected by the subject teacher who will discuss the students' problems, each student also receives the same question. SMA N 2 Kota Pariaman was chosen as a research location because this school has not used the Application during school exams, it is easy to achieve and economical. The application to be used can randomize randomly so that exam questions can be varied and dynamic. With the application of the application that is expected to carry out school examinations will be better and obtained optimally by students, teachers, school management and parents / guardians of students. For this reason, the authors will conduct research consisting of the design of Computer Based Test applications using the Coupled Linear Congruential Generator (CLCG) method. The development of the Computer Based Test (CBT) model by using a Coupled Linear Congruent Generator (CLCG) can prevent the questioning of questions for students. CLCG is a random number generator based on the Linear Congruent Generator (LCG). CLCG uses the xj matrix to get random numbers. organized by rows and columns. The matrix prefers a range of numbers and has no arithmetic relationship between its elements. The matrix will have different row and column addresses. The value of the elements of the matrix obtained from the process with the Linear Congruent Generator to get as many random numbers as is done. CBT is one way of overcoming questions in each student. The use of LCG in the matrix value element can have a more complicated random pattern. Reducing the question answer key by entering the answer key time after the exam is finished. Languages supported using the CLCG method can optimize student abilities and reduce the level of cheating. Reducing the question answer key by entering the answer key time after the exam is finished. Keywords: CBT Appliaction, Couple Linear Congruential Generator, Linear Congruential Generator, Random Number, School Exam.